Analgesic and antihyperalgesic effects of Scoparia dulcis decoction in rats - Ratnasooriya, W. D.; Galhena, G.; Liyanage, S. S. P.; Jayakody, J. R, A. C. (My University, 2002)
Scoparia dulcis Lin. (Family: Scrophulariaceae, Sinhala: Wal kottamalli) is a perennial herb commonly found in many tropical countries including Sri Lanka (Dassanayaka, 1981). In folk and traditional medicine in Brazil, it is widely used as an analgesic and this effect has been experimentally proven in mice (de Farias Freire, cl. Al, 1993). However, in the traditional Ayurvedic system of medicine in Sri Lanka S. dulcis is not used to alleviate pain (as an analgesic or/and antihyperalgesic) although, it is used in several other countries as in Brazil (ex. in diabetes mellitus) (de Farias Freire, et. A l , 1993). Is it due to lack of analgesic and/or antihyperalgesic P^itcntials in Sri lankan S. dulcis or due to possession of hyperalgesic activity? We thought it is worth examining ^cause if pain impairing activity is present in the local ^- ^"/c(".y plant, it could be used as a painkiller by Sri Lankan native physicians. As about 35% of the Sri Lankan population still principally depends on Ayurvedic ''•"t'it'onal systems of health care (Mahindapala, abu " ' ' ^ ' ' ^ ' ^ culturally acceptable. The plant is ^ndant in ''Kiges,!! also provides a .icapcr aiin"?^"^*^ ^ developing nation like Sri Lanka. The pi in" investigate whether local S. dulcis Usin '^'^^'^•'^•'^ P^'" relieving potential using rats and ^ P^iinl decoction (D).